Pola Komunikasi Interpersonal dalam Konflik Antara Pasangan Suami Istri Beda Budaya yang Baru Menikah - Kurniawati, Dessy (Jurnal The Messenger, 2013)
This research aims is to understand how marrying couples manage their conflict in the setting of cultural difference. The principal theory used in this research is Johari Window theory that explains connection between self and openness in individual communications. The methodology that used in this research is qualitative descriptive with interpretive perspective. This research is done at city of Semarang and use five couples as source. The couples itself do have setting on ethnical difference. From fifth marriage couples we can found that openness, support, and sincere positive attitude in family, gives big contribution to create good communication in a family. Based on the interview all of informants declare that their wedding life is goes on well and harmonic, despite of several problems. In a whole they have good marriage and doesn t find big conflict and or big problem that makes them lose communication each other, or with their larger family circle, or with society, despite their different ethnic background.